Peran Etika Bisnis dalam Membangun Kepercayaan Konsumen pada Pedagang Kaki Lima di Kota Dumai - Putri Sulisti; Hildawati Hildawati (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Street vendors play an essential role in urban informal economies by fulfilling community needs and supporting local economic activity. This study analyzes the role of business ethics in building consumer trust among street vendors in Dumai, Indonesia. A qualitative descriptive method was applied using interviews, observation, and documentation involving three vendors and two consumers. Findings indicate that ethical practices such as honesty in transactions, responsibility for product quality, friendly service, and cleanliness of business premises improve consumer comfort and perceived safety. These conditions encourage repeat purchases, customer loyalty, and a positive reputation for vendors. Therefore, business ethics function not only as moral guidance but also as social capital supporting the sustainability of informal microenterprises. This study highlights that ethical behavior is crucial for strengthening long-term relationships between vendors and consumers in urban settings. Overall, implementing ethical standards contributes to sustainable small business development in informal sectors. It also improves public trust.